PS-096 Profile of onco-haematological patients susceptible to dose-adjustment to renal function. (24th February 2014) - Soler Blanco, N; Pardo, C; Priegue, M; Rovira, O; Mas, MP
Abstract : Background: Renal impairment can alter excretion of chemotherapeutic agents and increase systemic toxicity. For that reason dose adjustment is often required in cancer patients treated with these drugs. It is important to know the patient's profile in order to prevent this toxicity. Purpose: To determine the patient profiles and chemotherapeutic regimens that might need adjustment due to kidney failure. Materials and methods: We carried out a study of onco-haematological patients in treatment between January–March 2013. The information was obtained from our Hospital databases including the prescription-validation-compounding integrated process. Kidney function data was obtained from the laboratory test results included in patients' electronic clinical history. Dose-adjustment factors were taken from the available literature. Results: 1293 treatments were validated with one or more chemotherapeutic agents. We reviewed serum creatinine levels in 273 treatments (21%). The mean age of patients with renal failure was 65.2 ± 11.3 years. 20 chemotherapeutic dose adjustments were suggested by the pharmacist: 4 carboplatin-etoposide regimen, 2 oxaliplatin and raltitrexed, 4 doxorubicin and bleomycin-vinblastine-dacarbazine, 4 etoposide, 3 rituximab-cyclophosphamide-vincristine-doxorubicin, 1 docetaxel-cyclophosphamide and 2 cisplatin. All of them were accepted. 22.2% of the raltitrexed prescriptions were adjusted, 20.6% of etoposide, 14.3% of bleomycin, 8.3% of dacarbazine and 4.5% of cisplatin prescriptions. 25% of cyclophosphamide in rituximab-cyclophosphamide-vincristine-doxorubicin regimens was adjusted. Conclusions: 7.3% (20/273) of the treatments during January–March 2013 were adjusted by pharmacist intervention. Dosage adjustment was mainly needed in mild-moderate renal failure patients reducing the dose by 20–25% in higher risk of nephrotoxicity drugs. Pharmacist interventions on pharmacotherapeutic monitoring of patients with chemotherapy improve patient safety and reduce the risk of toxicity. No conflict of interest.